Adsorption of catechol onto PEDOT films doped with gold nanoparticles: Electrochemical and spectroscopic studies. (1st November 2019) - Soares, Ana Leticia; Zamora, Martin L.; Marchesi, Luís F.; Vidotti, Marcio
Abstract: In this work, the electrochemical processes at the electrode/electrolyte interface of PEDOT:PSS modified electrodes were studied. A detailed investigation using Electrochemical Impedance Spectroscopy (EIS) was done to determine the adsorption and electrochemical effects caused by the interaction of catechol at the conductive substrate. Different parameters such as double-layer capacitance, charge transfer resistance and intercalation charge distribution were analyzed in the presence of different amounts of catechol in the electrolyte. It was found a direct response of the charge transfer resistance (Rct ) with catechol concentration, in the same way, the electrocatalytical response of the reversible redox reaction of catechol was observed. The investigation of the incorporation of gold nanoparticles (AuNPs) onto the PEDOT:PSS substrates showed an intrinsic increment in the conductivity, favoring the interaction between catechol and PEDOT, presenting an interesting tool for the construction of impedimetric sensors. The modified electrodes were further characterized by Scanning Electron Microscopy and Raman Spectroscopy.